Philosophy of Education in Today’s World and Tomorrow’s: A View from ‘Down Under’ - Clark, John (Paideusis, 2006)
In considering philosophy of education now and in the future, this paper explores the issue from an Australasian perspective. While philosophy of education in this part of the world has strong international links there is an absence of indigenous influences. A number of philosophical strands have developed including naturalism and postmodernism which have informed thinking about education policy and practice. The institutional side of philosophy of education has witnessed both the promotion of philosophers to professorial positions and the slow decline in numbers as departing staff are not replaced. How philosophy of education will fare in the future will depend on the survival of an academic community, the opportunity to teach papers in the subject to undergraduate and postgraduate students (and so replace ourselves) and convincing teachers and policy makers that philosophy of education makes an indispensable contribution to improving policy and the educational experiences of students.